Distinct Conformational States of the Alzheimer β‐Amyloid Peptide Can Be Detected by High‐Pressure NMR Spectroscopy1. Issue 34 (10th July 2013) - Munte, Claudia Elisabeth; Beck Erlach, Markus; Kremer, Werner; Koehler, Joerg; Kalbitzer, Hans Robert
<x xml:space="preserve">Abstract</x> Folding under pressure: High‐pressure NMR spectroscopy detects three different conformational states of the Aβ‐peptide in solution: a compactly folded state 1, a partially folded state 2′, and a random‐coil like state 2′′ (see plot, p=population). At ambient pressure the folded state 1 dominates which probably has a high affinity to fibrils and thus may promote fibril formation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>